2016
DOI: 10.1021/acs.jmedchem.6b00585
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity versus Flexibility: Is This an Issue in σ1 Receptor Ligand Affinity and Activity?

Abstract: Stereoisomeric 2,5-diazabicyclo[2.2.2]octanes 14 and 15 were prepared in a chiral-pool synthesis starting from (S)- or (R)-aspartate. The key step in the synthesis was a Dieckmann-analogous cyclization of (dioxopiperazinyl)acetates 8, which involved trapping of the intermediate hemiketal anion with Me3SiCl. The σ1 affinity was tested using membrane preparations from animal (guinea pig) and human origin. The binding of bicyclic compounds was analyzed by molecular dynamics simulations based on a 3D homology mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Moreover, the equation for calculating RMSF is shown below; and accordingly, to obtain the standardized RMSF (sRMSF), the average RMSF is deducted from RMSF i (RMSF of the ith residue) and further divided by its standard deviation. The RMSF parameter is used to monitor the motion or fluctuations of individual residues that constitute the protein molecule, giving overall insights into the characteristic flexibility or rigidity of such molecule [ 112 , 113 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the equation for calculating RMSF is shown below; and accordingly, to obtain the standardized RMSF (sRMSF), the average RMSF is deducted from RMSF i (RMSF of the ith residue) and further divided by its standard deviation. The RMSF parameter is used to monitor the motion or fluctuations of individual residues that constitute the protein molecule, giving overall insights into the characteristic flexibility or rigidity of such molecule [ 112 , 113 ]. …”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Weber et al reported the synthesis of 2,5-diazabicyclo[2.2.2]octane derivatives. 132 These compounds were designed for the same purposes previously discussed for the 7,9-diazabicyclo[4.2.2]decane series. The authors hypothesized that if rigidification of 28 into compound 29 afforded a 30-fold improvement of the σ 1 K i affinity value, then similar results should also be achieved by rigidification of the flexible (piperazin-2-yl)-ethanol structure (general structure in Figure 13 ) into the 2,5-diazabicyclo[2.2.2]octane scaffold (i.e., 38 – 43 , ent-38 – 43 , Figure 15 ).…”
Section: σR Ligands With Cytotoxic Effectsmentioning
confidence: 99%
“…Color-coded as follows: PI (red), HYAr or HYD (light blue), HY (pink), HBA (light green), π-interactions (Arg119 and Tyr120, cyan), salt bridge (Asp126, red), hydrophobic interactions (Ile128, Phe133, Tyr173, and Leu186, purple), and hydrogen bond (Thr181, green). Adapted with permission from ref ( 132 ). Copyright 2016 American Chemical Society.…”
Section: σR Ligands With Cytotoxic Effectsmentioning
confidence: 99%
“…Recently, a new synthetic class of σ 1 receptor ligands have been obtained and studied using molecular dynamics (MD) simulations with a homology model of the receptor [ 25 ]. This class of receptor has been developed using as templates the 3D structures of four different proteins, structure–affinity relationships, pharmacophore models, and the mutagenesis data as used by Brune et al [ 2 , 4 ], Laurini et al [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and other research groups [ 7 ]. These compounds are alkyl and arylcarboxamide derivatives [ 32 ], arylalkylamines [ 30 ], benzoxazolones, and dioxolane-based compounds [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could be partly because this receptor does not share a sequence homology with any other mammalian protein [ 7 ]. Moreover, this could also be because the recently published X-ray data for the σ 1 receptor show “little similarity to previous computational models“ [ 1 , 5 ] used so far in homology-based studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Here we focus on the σ 1 receptor for which crystal structural data are available for the first time.…”
Section: Introductionmentioning
confidence: 99%